2006
DOI: 10.1016/j.hepres.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Virological effects and safety of combined double filtration plasmapheresis (DFPP) and interferon therapy in patients with chronic hepatitis C: A preliminary study

Abstract: Purpose: In patients with chronic genotype 1b hepatitis C and a high viral load, the viral load was reduced by double filtration plasmapheresis (DFPP), followed by combined interferon and ribavirin therapy. The safety and virological effects of this treatment method were preliminarily investigated. Methods:In 9 patients with chronic hepatitis C, DFPP was performed 3 times on days 1, 2, and 4, and the administration of interferon and ribavirin was initiated immediately after DFPP on day 1. Result:The HCV RNA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…Several studies have reported the use of DFPP for HCV treatment [4][5][6]. Fujiwara et al [4] demonstrated that DFPP plus IFN combination therapy produced a considerable reduction in the viral load during the early stage of treatment and yielded a high SVR rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the use of DFPP for HCV treatment [4][5][6]. Fujiwara et al [4] demonstrated that DFPP plus IFN combination therapy produced a considerable reduction in the viral load during the early stage of treatment and yielded a high SVR rate.…”
Section: Discussionmentioning
confidence: 99%
“…VRAD therapy was administered as described previously [4][5][6]. A Plasmaflo TM OP-08W (Asahi Kasei Medical) and an Evaflux TM 5A20 (Asahi Kasei Medical) were used as the plasma separator (first filter) and plasma fractionator (second filter), respectively.…”
Section: Case Reportmentioning
confidence: 99%
“…DFPP replacement fluid was not required. DFPP was performed a total of five times over a period of two weeks, but never on more than two consecutive days in order to prevent the blood fibrinogen levels decreasing to <100 mg/dl (9).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment by plasma aphaeresis has been used effectively on patients afflicted with hepatitis C infection [11]- [14], and cancer [15]. In plasma aphaeresis, the virus particles in the larger components of the plasma are removed from a patient, after which the small molecular components of plasma and cellular components of the blood are returned to the patient.…”
Section: Introductionmentioning
confidence: 99%